5-Aminolevulinic acid hydrochloride loaded microbubbles-mediated sonodynamic therapy in pancreatic cancer cells. Issue 1 (1st January 2020) - Yang, Wei; Xu, Haitao; Liu, Qinghao; Liu, Chunxun; Hu, Jiahe; Liu, Ping; Fang, Tianyi; Bai, Yuxian; Zhu, Jiuxin; Xie, Rui
Abstract: 5-Aminolevulinic acid hydrochloride (ALA)-mediated sonodynamic therapy (SDT) had anti-tumour effect on pancreatic cancer cells. Hence, ALA loaded lipid/poly(lactic-co-glycolic acid) (PLGA) microbubbles (MBs)-mediated SDT for pancreatic cancer has great potential. The average size of ALA-lipid MBs and ALA-PLGA MBs was about 3.0 µm. The two kinds of MBs had good biocompatibility to normal HPDE6-C7 cells and were not toxic to pancreatic cancer cells. Compared with ALA-induced SDT, a statistically significant decrease in cell viability was observed in ALA lipid/PLGA MBs combined with ultrasound groups in AsPC-1 and BxPC-3 cells ( p < .05). Obvious effect on the apoptotic rate, apoptosis and pyroptosis morphology, enhanced reactive oxygen species was found in ALA-lipid/PLGA MBs mediated SDT in vitro . Through in vivo study, we found ALA-lipid/PLGA MBs-mediated SDT was a promise treatment for pancreatic cancer.